IMPLEMENTASI METODE AGILE SCRUM PADA SISTEM INFORMASI LEMBAGA SERTIFIKASI PROFESI SMK XYZ MENGGUNAKAN FRAMEWORK LARAVEL - Wisnu Ahmat Umar; Dina Pratiwi; Adika Rafiq Wicaksana; Lukman Lukman (Unit Penelitian, Pengabdian Kepada Masyarakat dan Penjamnan Mutu Akademi Komunitas Negeri Pacitan, 2026)
The presence of a Professional Certification Institute (LSP) at a Vocational High School (SMK) is a necessary supplement in efforts to improve the quality of the school and its students. Unfortunately, many schools do not yet have a supporting information system to handle and manage these business processes. This study focuses on analyzing and implementing the Agile Scrum development method to build a Professional Certification Institute (LSP) Competency Test Information System at SMK. This LSP plays a very important role in testing student abilities, therefore an efficient and adaptive information system is needed to support the continuity of the competency test to be more optimal. The use of the Agile Scrum development method was chosen because this method can focus on rapid iteration and can collaborate between the development team and users on an ongoing basis. The design of this information system was built using the Laravel Framework to maximize security, ease of maintenance and optimize its performance. The resulting information system will be functionally tested with Blackbox and other parameters with Roger Pressman web application testing. Quantitative results are presented on a Likert scale to indicate the general quality of the system.